2012
DOI: 10.1097/nen.0b013e31826caebe
|View full text |Cite
|
Sign up to set email alerts
|

Time Course and Spatial Profile of Nogo-A Expression in Experimental Autoimmune Encephalomyelitis in C57BL/6 Mice

Abstract: Inhibition of the myelin-associated neurite outgrowth inhibitor Nogo-A has been found to be beneficial in experimental autoimmune encephalomyelitis (EAE), but there are little data on its expression dynamics during the disease course. We analyzed Nogo-A mRNA and protein during the course of EAE in 27 C57BL/6 mice and in 8 controls. Histopathologic and molecular analyses were performed on Day 0 (naive), preclinical (Day 10), acute (Days 18-22) and chronic (Day 50) time points. In situ hybridization and real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 57 publications
6
36
0
8
Order By: Relevance
“…This is consistent with findings in EAE mice [89]. Elevated serum and cerebrospinal fluid (CSF) autoantibody levels against the large N-terminal domain of Nogo-A have been found in blood samples from MS patients [101], but anti-Nogo-A antibodies exist also in healthy controls.…”
Section: The Role Of Nogo-a In Multiple Sclerosissupporting
confidence: 77%
See 1 more Smart Citation
“…This is consistent with findings in EAE mice [89]. Elevated serum and cerebrospinal fluid (CSF) autoantibody levels against the large N-terminal domain of Nogo-A have been found in blood samples from MS patients [101], but anti-Nogo-A antibodies exist also in healthy controls.…”
Section: The Role Of Nogo-a In Multiple Sclerosissupporting
confidence: 77%
“…Interestingly, Nogo-A mRNA and protein levels were observed to be inversely correlated with those of the axonal growth marker GAP43 at different stages of the course of EAE [89]. This work showed that Nogo-A mRNA expression is reduced at preclinical and acute phases, which is followed by upregulation of mRNA and protein during the chronic EAE stage.…”
Section: The Role Of Nogo-a In Neuro-inflammatory and Demyelinating Cmentioning
confidence: 60%
“…Inflammatory lesions of these diseases have been shown to result in demyelination and axonal damage, and inhibition of the NogoA-NgR-RhoA signaling pathways prevents new growth cone formation (Satoh et al, 2005;Zhang et al, 2008). In addition, increased NogoA and NgR mRNA and protein have been observed in the chronic phase of EAE (Theotokis et al, 2012). In the study, accumulation of RhoA ( þ) cells was maximal in EAE rat brains during the acute stage, and this upregulation was sustained until the recovery stage of the disease.…”
Section: Discussionmentioning
confidence: 97%
“…Blockade of the downstream signaling pathway of Nogo-A by changing the phosphorylation status of CRMP-2 was reported beneficial to MS [50]. Nogo-A and its receptors were once only believed to be up-regulated in the demyelinating lesions of MS [8], but they are now also found to be related with the progression of EAE [7]. The Ozanezumab (GSK1223249), an anti-Nogo-A antibody which is produced by GlaxoSmithKline in the treatment of MS and ALS is now under phase II clinical trials [139].…”
Section: Multiple Sclerosismentioning
confidence: 96%
“…It also plays a critical role in the regulation of adhesive and repulsive interactions between cells in radial migration during cortical development [5], as well as in the regulation of synaptic plasticity and cognitive functions, from many aspects such as the dendritic morphology, synaptic transmission, intrinsic excitability and spontaneous firing, which when blocked would finally result in distinct behaviors resembling neuropsychiatric phenotypes [6]. For example, both Nogo-A and NgR were found to be up-regulated in EAE [7] and MS [8]. Accumulation of myelin debris from the oligodentrocytes that highly express Nogo-A and other myelin-derived inhibitory protein like MAG and OMgp, would play a critical role in the axonal growth inhibition, and the debris might also inhibit other oligodentrocytes' remyelination on the naked axon [9].…”
Section: Introductionmentioning
confidence: 98%